The dividend payout policy - a study on Malaysian financial institutions - Hutagalung, S.; Yahya, Mohamed Hisham; Kamarudin, Fakarudin; Osman, Z. (Universiti Putra Malaysia Press, 2013)
The purpose of this study is to identify the determinants of dividend policy in Malaysian financial institutions. Panel data set were constructed from 33 financial institutions in Malaysia for a period of 10 years (2001-2010). The results show a statistically significant positive relationship between dividend policy and profitability, which implies that Malaysian financial institutions distribute higher dividends when they record higher profitability. Lagged dividend also shows a positive significant relationship with dividend policy, which implies that financial institutions in Malaysia follow a stable dividend policy that maintains regularity of dividend payments with gradual adjustments of dividend payments towards the target payout. On the other hand, leverage shows a significant negative relationship with dividend policy, which means that a riskier financial institution pays out lower dividends. In conclusion, profitability, lagged dividend and leverage are found to be the major determinants of dividend policy in relation to Malaysian financial institutions. The results support the agency cost theory, signaling theory and the free cash flow hypothesis.